Interconnectedness of the banking sector as a vulnerability to crises - Tuomas A. Peltonen; Michela Rancan; Peter Sarlin (European Central Bank (ECB), 2015)
This paper uses domestic and cross-border linkages to measure the interconnectedness of the banking sector, and relates it to banking crises in Europe. Beyond cross-border financial linkages of the banking sector, we also account for financial linkages to the other main financial and non-financial sectors within the economy. We enrich conventional early-warning models using macro-financial vulnerabilities, by including measures of banking sector centrality as potential determinants of banking crises. Our results show that a more central position of the banking sector in these so-called macro-networks significantly increases the probability of a banking crisis. By analyzing the different types of risk exposures, our evidence shows that credit as well as market risks are important sources of vulnerabilities. Finally, the results show that early-warning models augmented with interconnectedness measures outperform traditional models in terms of out-of-sample predictions of recent banking crises in Europe.
Keywords: F36; G20; 330; Banking crises; Early-warning model; Financial interconnectedness; Macro-networks